PENGARUH KECINTAAN UANG TERHADAP PENGGELAPAN PAJAK DENGAN RELIGIUSITAS DAN MATERIALISME SEBAGAI VARIABEL MODERASI - Tanra, Andi Ainil Mufidah; Yuniar, Latifah Sukmawati; Afdalia, Nadhira; Farid, Erwan Sastrawan; Iqbal, Muhammad; Muslimin, Ulfah Rizky; Nichen, Nichen (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
A decrease in the amount of tax revenue can occur due to tax evasion by taxpayers. Tax evasion actions carried out by taxpayers can be influenced by a lack of understanding of taxation knowledge, not optimal tax service services, tax sanctions that do not provide a deterrent effect for taxpayers, and high love of money. This study aims to examine the effect of the love of money on tax evasion, moderated by the variables of religiosity and materialism. A quantitative approach is used in this study. The sample is 365 individual taxpayers. The sampling technique used is simple random sampling. Moderated Regression Analysis (MRA) was used to analyze the data of this study. This study indicates that the love of money has a significant and significant effect on tax evasion. The relationship between the love of money and tax evasion is moderated by religiosity. The relationship between the love of money and tax evasion is also moderated by materialism.